1994
DOI: 10.1111/j.1460-9568.1994.tb00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Properties of Neuronal Nicotinic Receptors Reconstituted from the Vertebrate β2 Subunit and Drosophilaα Subunits

Abstract: Three cDNAs (ALS, D alpha 2 and ARD) isolated from the nervous system of Drosophila and encoding putative nicotinic acetylcholine receptor subunits were expressed in Xenopus oocytes in order to study their functional properties. Functional receptors could not be reconstituted from any of these subunits taken singly or in twos and threes. In contrast, large evoked currents (in the microA range) were consistently observed upon agonist application on oocytes co-injected with ALS or D alpha 2 in combination with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
129
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 42 publications
14
129
1
1
Order By: Relevance
“…In addition, Xenopus oocytes have been used successfully to examine nAChR subunits cloned from several invertebrate species, including the aphid Myzus persicae [89], the brown planthopper Nilaparvata lugens [90], the fruit fly Drosophila melanogaster [69,91], the locust Schistocerca gregaria [92] and the nematode Caenorhabditis elegans [93,94]. Frustratingly, the heterologous expression of invertebrate nAChRs has proved to be extremely difficult [59,95] and, in several instances, this has often been achieved only by co-expression with vertebrate nAChR subunits [65,91,96,97]. More recently, expression studies in Xenopus oocytes have identified a family of anion-selective nAChRs, cloned from both the nematode Caenorhabditis elegans [98] and the mollusc Lymnaea stagnalis [99,100].…”
Section: Expression Of Recombinant Nachrs In Xenopus Oocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Xenopus oocytes have been used successfully to examine nAChR subunits cloned from several invertebrate species, including the aphid Myzus persicae [89], the brown planthopper Nilaparvata lugens [90], the fruit fly Drosophila melanogaster [69,91], the locust Schistocerca gregaria [92] and the nematode Caenorhabditis elegans [93,94]. Frustratingly, the heterologous expression of invertebrate nAChRs has proved to be extremely difficult [59,95] and, in several instances, this has often been achieved only by co-expression with vertebrate nAChR subunits [65,91,96,97]. More recently, expression studies in Xenopus oocytes have identified a family of anion-selective nAChRs, cloned from both the nematode Caenorhabditis elegans [98] and the mollusc Lymnaea stagnalis [99,100].…”
Section: Expression Of Recombinant Nachrs In Xenopus Oocytesmentioning
confidence: 99%
“…Hybrid nAChRs that contain both insect and vertebrate nAChR subunits have also been used extensively in an attempt to circumvent problems encountered with the inefficient heterologous 12 expression of insect nAChRs [59,95]. This approach has been adopted for studies of nAChRs cloned from insect species, including the aphid Myzus persicae [150,151], the brown planthopper Nilaparvata lugens [90,97], the cat flea Ctenocephalides felis [152] and the fruit fly Drosophila melanogaster [91,96,118,153].…”
Section: The Influence Of Subunit Compositionmentioning
confidence: 99%
“…This clearly implies a different mode of binding and/or channel modulation for DNF in comparison to the other neonicotinoids. 21,67) As demonstrated in Xenopus oocytes with wildtype Nlα1, DNF clearly has the potential to interact at the same nAChRs as the other neonicotinoids, although (as observed with TMX) the influence of native insect β receptors is unknown. This data strongly suggests that the specific amino acids of the nAChR that are involved in DNF recognition and/or channel modulation have differences to that of the other neonicotinoids.…”
Section: Thiamethoxammentioning
confidence: 99%
“…3). 21,22) The reasons behind this are not well understood but the correct combination of nAChR subunits with corresponding chaperone proteins in the adequate cellular background may be required to form the functional receptor. Therefore, to date, knowledge on insect nAChR pharmacology has been principally derived from radioligand binding studies on native insect homogenates combined with direct electrophysiological recordings from exposed/isolated nervous tissue and heterologous expression studies with co-expressed mammalian/avian β subunits.…”
Section: Invertebrate Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation